Cross-Leg Free Flap: Crossing the Border Zone of Ischemic Limb—A Case Report of Limb Salvage Procedure following a Delayed Diagnosis of Popliteal Artery Injury - Lam, Hui Yuan; Sulaiman, Wan Azman Wan; Ismail, Wan Faisham Wan; Halim, Ahmad Sukari (Archives of Plastic Surgery, 2023)
Vascular injury following traumatic knee injury quoted in the literature ranges from 3.3 to 65%, depending on the magnitude and pattern of the injury. Timely recognition is crucial to ensure the revascularization is done within 6 to 8 hours from the time of injury to avoid significant morbidity, amputation, and medicolegal ramifications. We present a case of an ischemic limb following delayed diagnosis of popliteal artery injury after knee dislocation. Even though we have successfully repaired the popliteal artery, the evolving ischemia over the distal limb poses a reconstruction challenge. Multiple surgical debridement procedures were performed to control the local tissue infection. Free tissue transfer with chimeric latissimus dorsi flap was done to resurface the defect. However, the forefoot became gangrenous despite a free muscle flap transfer. His limb appeared destined for amputation in the vicinity of tissue and recipient vessels, but we chose to use a cross-leg free flap as an option for limb salvage.
Keywords: popliteal artery; free flap; lower limb; knee dislocation